...e o vento não levou: construindo o imaginário urbano carioca - Borde, Andréa de Lacerda Pessôa (1998)
We imagined and searched for new possibilities of understanding the urban imaginary beyond its artistic representations. Our analyses of the urban imaginary are based on the concepts of Art Anthropology. From this point of view, we pinpointed not only the urban dimension of the imaginary, but also the imaginary dimension of the urban. We walked through imaginary cities and mapped studies on urban imaginary. Following, we analysed the configuring elements of Rio´s urban imaginary, guided by cinema and architecture, we looked for the motives and complexities of its construction, at the dawn of the twentieth century. Secondly, we wandered along Lapa´s borough shooting photos and creating mouldings in ceramics. We meant to fundament new possibilities of research on Art Anthropology, articulating it with urban issues.